Time-loss injuries in sub-elite and emerging Rugby League players - Booth, M.; Orr, R. (Journal of Sports Science & Medicine, 2017)
This study aimed to 1) investigate the incidence and characteristics of injuries in emerging rugby league players; and 2) explore the differences in injury incidence and characteristics between the various sub-elite competitions. An NRL emerging player development squad (n = 34) was observed from the beginning of pre-season until the finish of competition. Time-loss injury was defined as any physical pain or impairment sustained that resulted in players missing a match. Injuries were categorised according to circumstance, incidence, characteristics, playing position and competition level. Of a total of 196 injuries that were recorded, 45 were time-loss and 151 were transient. The total injury incidence was 7.9/1,000 playing hours. The most common sites for time-loss injuries were the shoulder, ankle/foot and knee. Ligament injuries accounted for the highest number of injuries by type. Forwards sustained the greatest number of injuries. However, backs suffered the greatest injury cost. The majority of time-loss injuries were sustained during competition matches. Injuries sustained during open age matches resulted in significantly higher injury cost to those received at NYC matches. NRL development and emerging rugby league players are exposed to high risk of injury. Lower limb and shoulder injuries to bone or connective tissue are prevalent as a result of contact during match play. Players at this developmental level feed into several different playing squads where disparities in physical development, maturation, playing intensity and training regimes are evident. This presents a challenge in matching physiological capabilities with playing demands for NRL development squads. Key Points: